In The Context of Developing the Digital Economy Modern Forms of Employment - Nishonqulov Shohruhxon Farxodjon Ogli; Rajabboyev Botir Odil Ogli (Genius Publishing Group, 2021)
The accelerated development of digital technologies leads to increased employee mobility and the creation of qualitatively new jobs. The current stage of development of the world economy requires the development of modern forms of employment, in particular, the development of distance employment. Based on this, this article analyzes the possibilities of using modern forms of employment in the conditions of the Republic of Uzbekistan and develops recommendations.
Keywords: development; jobs; digital; technologies